Pengaruh Kualitas Produk Dan Kualitas Layanan Terhadap Kepuasan Konsumen King Cake - Monica Maria; Mohamad Yusak Anshori (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2013)
The main purpose of this research is to identify the influence of product quality (X1) and service quality (X2) towards King Cake’s customer satisfaction (Y). The population of this research is King Cake’s customers. The sample size is 63 respondents. Respondents are selected using non-probability sampling, which is Purposive Sampling. This research uses multiple linear regression analysis. The validity and reliability testing to each indicator is taken before performing the multiple linear regression analysis. The research shows that  product quality (X1) and service quality (X2) significantly influences King Cake’s customer satisfaction (Y). The finding shows that service quality (X2) gives more significant value towards customer satisfaction (Y) than product quality (X1) does.